Corrigendum to ‘Corenet: A flexible framework for generating and prioritising core cycle network designs’ [Journal of Transport Geography 122 (2026) 104148] - Zhao Wang; Hang Hu; Hussein Mahfouz; Juan Pablo Fonseca-Zamora; Martin Lucas-Smith; Dustin Carlino; Angus Calder; Congying Hu; Matthew Davis; Joseph Talbot; Robin Lovelace (Journal of Transport Geography, 2026)

Corenet: A flexible framework for generating and prioritising core cycle network designs - Zhao Wang; Hang Hu; Hussein Mahfouz; Juan Pablo Fonseca-Zamora; Martin Lucas-Smith; Dustin Carlino; Angus Calder; Congying Hu; Matthew Davis; Joseph Talbot; Robin Lovelace (Journal of Transport Geography, 2026)

Azole‐resistant Aspergillus fumigatus is highly prevalent in the environment of Vietnam, with marked variability by land use type - Tra‐My N. Duong; Thanh‐Van Le; Khanh‐Linh H. Tran; Phuong‐Tuyen Nguyen; Bich‐Phuong T. Nguyen; Thu‐Anh Nguyen; Huong‐Lan P. Nguyen; Bich‐Ngoc T. Nguyen; Matthew C. Fisher; Johanna Rhodes; Guy Marks; Greg J. Fox; et al. (Environmental Microbiology, 2021)
Summary Azole‐resistant environmental Aspergillus fumigatus presents a threat to public health but the extent of this threat in Southeast Asia is poorly described. We conducted environmental surveillance in the Mekong Delta region of Vietnam, collecting air and ground samples across key land‐use types, and determined antifungal susceptibilities of Aspergillus section Fumigati (ASF) isolates and azole concentrations in soils. Of 119 ASF isolates, 55% were resistant (or non‐wild type) to itraconazole, 65% to posaconazole and 50% to voriconazole. Azole resistance was more frequent in A. fumigatus sensu stricto isolates (95%) than other ASF species (32%). Resistant isolates and agricultural azole residues were overrepresented in samples from cultivated land. cyp51A gene sequence analysis showed 38/56 resistant A. fumigatus sensu stricto isolates carried known resistance mutations, with TR 34 /L98H most frequent (34/38).

Myocardial Perfusion Simulation for Coronary Artery Disease: A Coupled Patient-Specific Multiscale Model - Lazaros Papamanolis; Hyun Jin Kim; Clara Jaquet; Matthew Sinclair; Michiel Schaap; Ibrahim Danad; Pepijn van Diemen; Paul Knaapen; Laurent Najman; Hugues Talbot; Charles A. Taylor; Irene Vignon-Clementel (Annals of Biomedical Engineering, 2021)
Patient-specific models of blood flow are being used clinically to diagnose and plan treatment for coronary artery disease. A remaining challenge is bridging scales from flow in arteries to the micro-circulation supplying the myocardium. Previously proposed models are descriptive rather than predictive and have not been applied to human data. The goal here is to develop a multiscale patient-specific model enabling blood flow simulation from large coronary arteries to myocardial tissue. Patient vasculatures are segmented from coronary computed tomography angiography data and extended from the image-based model down to the arteriole level using a space-filling forest of synthetic trees. Blood flow is modeled by coupling a 1D model of the coronary arteries to a single-compartment Darcy myocardium model. Simulated results on five patients with non-obstructive coronary artery disease compare overall well to [ $$^{15}$$ 15 O] $$\text {H}_{{2}}$$ H 2 O PET exam data for both resting and hyperemic conditions. Results on a patient with severe obstructive disease link coronary artery narrowing with impaired myocardial blood flow, demonstrating the model’s ability to predict myocardial regions with perfusion deficit. This is the first report of a computational model for simulating blood flow from the epicardial coronary arteries to the left ventricle myocardium applied to and validated on human data.

Development and characterization of 12 polymorphic microsatellite loci in the sea sandwort, Honckenya peploides - Meg C. Gravley; George K. Sage; Sandra L. Talbot; Matthew L. Carlson (Journal of Plant Research, 2018)

Carbon accumulation of tropical peatlands over millennia: a modeling approach - Sofyan Kurnianto; Matthew Warren; Julie Talbot; Boone Kauffman; Daniel Murdiyarso; Steve Frolking (Global Change Biology, 2015)
Tropical peatlands cover an estimated 440 000 km 2 (~10% of global peatland area) and are significant in the global carbon cycle by storing about 40–90 Gt C in peat. Over the past several decades, tropical peatlands have experienced high rates of deforestation and conversion, which is often associated with lowering the water table and peat burning, releasing large amounts of carbon stored in peat to the atmosphere. We present the first model of long‐term carbon accumulation in tropical peatlands by modifying the Holocene Peat Model ( HPM ), which has been successfully applied to northern temperate peatlands. Tropical HPM ( HPMT rop) is a one‐dimensional, nonlinear, dynamic model with a monthly time step that simulates peat mass remaining in annual peat cohorts over millennia as a balance between monthly vegetation inputs (litter) and monthly decomposition. Key model parameters were based on published data on vegetation characteristics, including net primary production partitioned into leaves, wood, and roots; and initial litter decomposition rates. HPMT rop outputs are generally consistent with field observations from Indonesia. Simulated long‐term carbon accumulation rates for 11 000‐year‐old inland, and 5 000‐year‐old coastal peatlands were about 0.3 and 0.59 Mg C ha −1 yr −1 , and the resulting peat carbon stocks at the end of the 11 000‐year and 5 000‐year simulations were 3300 and 2900 Mg C ha −1 , respectively. The simulated carbon loss caused by coastal peat swamp forest conversion into oil palm plantation with periodic burning was 1400 Mg C ha −1 over 100 years, which is equivalent to ~2900 years of C accumulation in a hectare of coastal peatlands.

Development and characterization of 16 polymorphic microsatellite loci for the Alaska blackfish (Esociformes: Dallia pectoralis) - Matthew A. Campbell; George K. Sage; Rachel L. DeWilde; J. Andrés López; Sandra L. Talbot (Conservation Genetics Resources, 2014)

Large group of pygmy right whales seen in a shelf upwelling region off Victoria, Australia - Peter C. Gill; Catherine M. Kemper; Matthew Talbot; Susie A. Lyons (Marine Mammal Science, 2008)

Characterisation of novel point mutations in the survival motor neuron gene SMN , in three patients with SMA - Leigh Skordis; Matthew Dunckley; Lydia Burglen; Louise Campbell; Kevin Talbot; Shobna Patel; Judith Melki; Kay Davies; Victor Dubowitz; Francesco Muntoni (Human Genetics, 2001)